PRINCIPALS’ AND DIRECTORS’ PERCEPTIONS OF THE BARRIERS THAT INHIBIT FACULTY MEMBERS’ PARTICIPATION IN PROFESSIONAL DEVELOPMENT ACTIVITIES: A QUALITATIVE STUDY AT THE UNIVERSITY OF EDUCATION, LAHORE - Dr. Sumera Rashid; Dr. Sadia Afzal2; Fiza Zia (International Journal of Contemporary Issues in Social Sciences, 2024)
This study designed to investigate the perspectives of university directors and principals regarding the barriers that inhibit faculty members from participating in professional development activities. Gaining insight into these barriers is crucial for expanding teacher participation in professional development and uplifting the overall quality of education. The nature of this paper is Qualitative and adheres to the interpretive research paradigm. Using a purposive sampling technique, the researchers selected seven directors and principals from various divisions and campuses of the University of Education, Lahore, as participants. Moreover, following an extensive examination of relevant literature, researchers developed a semi-structured interview guide for the data collection, and interviews were conducted until saturation occurred. After that, the data were analyzed using thematic analysis and NVivo 11 plus software. The interview schedules were transcribed and then converted into a different script to carry out a thematic analysis of the data. Codes were assigned to the themes, and sub-themes were identified through the data analysis conducted on the interviews. Consequently, two significant themes emerged personal and professional barriers. The study’s findings highlighted several critical barriers, including heavy workload, additional administrative and non-teaching tasks, less financial incentives, lack of physical facilities, and barriers to professional development opportunities. Considering the results according to the principles and directors’ insights, institutional reforms are necessary to include reducing workloads and administrative work, increasing funding, improving institutional infrastructure, offering more consistent professional development (PD) opportunities, promoting research culture, and developing pertinent research-related professional development programs. Further, to create a more conducive environment for ongoing professional development, the University of Education, Lahore, can overcome these barriers. This would ultimately result in improved teaching and research quality and increased student educational achievements.